2016
DOI: 10.7150/thno.15311
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Peptide Receptor Radionuclide Therapy by the PARP Inhibitor Olaparib

Abstract: Metastases expressing tumor-specific receptors can be targeted and treated by binding of radiolabeled peptides (peptide receptor radionuclide therapy or PRRT). For example, patients with metastasized somatostatin receptor-positive neuroendocrine tumors (NETs) can be treated with radiolabeled somatostatin analogues, resulting in strongly increased progression-free survival and quality of life. There is nevertheless still room for improvement, as very few patients can be cured at this stage of disease. We aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 23 publications
2
101
1
1
Order By: Relevance
“…To improve the therapeutic efficacy of PRRT in NETs, different strategies have been investigated as follows: several clinical studies using fluoropyrimidine-based chemotherapy regimens for PRCRT in NET patients (3,(5)(6)(7)(8), preclinical studies using epigenetic modifiers as DNMT inhibitors/HDAC inhibitors to upregulate SSTR expression (12,13) and radioligand binding (12,13), preclinical studies using novel molecular target compounds for PRCRT (17)(18)(19), and variation of radiopharmaceuticals by the use of the a-emitters 215 Act or 213 Bis (20) or by the use of somatostatin antagonists (21). In preclinical studies, Taelman et al (12) and Veenstra et al (13) reported that several DNMT inhibitors and HDAC inhibitors induce SSTR mRNA transcription and protein expression and enhance specific SSTR-mediated radioligand binding of NET cells.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the therapeutic efficacy of PRRT in NETs, different strategies have been investigated as follows: several clinical studies using fluoropyrimidine-based chemotherapy regimens for PRCRT in NET patients (3,(5)(6)(7)(8), preclinical studies using epigenetic modifiers as DNMT inhibitors/HDAC inhibitors to upregulate SSTR expression (12,13) and radioligand binding (12,13), preclinical studies using novel molecular target compounds for PRCRT (17)(18)(19), and variation of radiopharmaceuticals by the use of the a-emitters 215 Act or 213 Bis (20) or by the use of somatostatin antagonists (21). In preclinical studies, Taelman et al (12) and Veenstra et al (13) reported that several DNMT inhibitors and HDAC inhibitors induce SSTR mRNA transcription and protein expression and enhance specific SSTR-mediated radioligand binding of NET cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, potentiating the cytotoxic effects of radiotherapy through radiosensitization, the therapeutic effects of radiotherapy may be improved [13]. Compounds that target the DNA-damage response mechanisms initiated as a result of ionizing radiation are of particular interest for use in combination with radiotherapy [14,15]. At the very center of the radiation response pathways is the well-known transcription factor p53 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly targeted therapeutics may be important to attain synergy with PRRT. For instance, concurrent inhibition of the DNA repair mechanisms with a poly-[ADP-ribose]-polymerase 1 inhibitor results in increased DNA double-strand breaks (23).…”
Section: Combination Therapymentioning
confidence: 99%